Initial stages of GaAs/Au eutectic alloy formation for the growth of GaAs nanowires - Rosnita, M; Yussof, W; Zuhairi,; Zulkafli, O; Samsudi, S (Universiti Kebangsaan Malaysia, 2012)
Annealing temperature plays an important role in the formation of an Au-Ga eutectic alloy. The effects of the annealing temperature on gold nanoparticles colloid and substrate surface were studied using AFM, FE-SEM and TEM. At 600oC, the layer of gold colloids particle formed an island in the state of molten eutectic alloy and absorbed evaporated metal-organics to formed nanowire (NW) underneath the alloy. Pit formed on the substrate surface due to the chemical reactions during the annealing process have an impact on the direction of growth of the NW. Without annealing, the NW formed vertically on the GaAs (100) surface. The growth direction depends on the original nucleation facets and surface energy when annealed. When annealed, the wire base is large and curved due to the migration of Ga atoms on the substrate surface towards the tip of the wire and the line tension between the substrate surface and gold particle.